1988
DOI: 10.1302/0301-620x.70b2.3346289
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary locking nails in the management of femoral shaft fractures

Abstract: Intramedullary locking nails have proved to be of considerable advantage when treating complex, comminuted or segmental femoral shaft fractures. We have reviewed 117 patients with 120 femoral shaft fractures treated with the Strasbourg device. These included 20 compound fractures, 13 pathological fractures and two non-unions. Rehabilitation and union rates have been very satisfactory and there have been no serious infections in the series. Comminution of the proximal femur has occurred in six patients and ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
0
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(50 citation statements)
references
References 0 publications
1
44
0
5
Order By: Relevance
“…In the literature, Christie et al [29] report that the healing time using the closed technique was 17 weeks, Johnson et al [30] report that the healing time using the closed technique was 13.8 weeks. Harper reported that healing time of closed and open method was 14.3 and 13.9 weeks, respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, Christie et al [29] report that the healing time using the closed technique was 17 weeks, Johnson et al [30] report that the healing time using the closed technique was 13.8 weeks. Harper reported that healing time of closed and open method was 14.3 and 13.9 weeks, respectively [9].…”
Section: Discussionmentioning
confidence: 99%
“…[7,8,[40][41][42][43] The nonunion rate of plate-screw fixation was reported as between 0% and 19%. [15,21,22,34,38,44] In our study, there was no nonunion in Group II, but 2 nonunion cases were detected in Group I.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6] After observing the better results with closed intramedullary nailing (IMN) in comminuted fractures, priority changed from a mechanical to biological basis. [7][8][9][10] With biological aspects, attention has shifted from absolute anatomic reduction and stability toward the preservation of tissue vascularity while obtaining anatomic alignment and relative stability. [6,11] Biological internal fixation avoids the need for precise reduction, especially of the intermediate fragments, and has the advantage of indirect reduction.…”
mentioning
confidence: 99%
“…IM nailing has good overall outcomes, with union rates above 90%, decreased infection rates and early functional use of the leg. 4,5 Because of the good outcomes of closed reduction and IM nailing, plating is reserved mostly for periprosthetic fractures, cases of patients with small intramedullary canals and cases of ipsilateral neck-shaft fractures. 6 Despite its high success rate, closed reduction is technically challenging and it is associated with unwanted side effects, such as high intraoperative radiation exposure and postoperative rotational malalignment.…”
Section: Introductionmentioning
confidence: 99%